Minimally invasive treatment of oral ranulae: adaption to an old technique. Issue 4 (April 2015) - Goodson, A.M.C.; Payne, K.F.B.; George, K.; McGurk, M.
Abstract Oral ranulas are cysts in the floor of the mouth that result from the extravasation of mucous. Historically there has been little consensus on the ideal first-line treatment, but currently, definitive treatment involves excision of the sublingual gland, which can injure the lingual nerve and submandibular duct. Minimally invasive surgical alternatives such as marsupialisation have been proposed, but so far have been associated with a high rate of recurrence. The aim of this pilot study was to evaluate the success of a simple, modified suture technique for the treatment of oral ranulas that can be done in the outpatient department. We retrospectively analysed outcomes after the technique was used as a first-line treatment in 15 consecutive patients between 2011 and 2013. Although 2 attempts were needed in 4 patients, complete resolution of the ranula was seen in 13. Other than the need for a second attempt, and recurrent failure in 2 cases, there were no complications. This minimally invasive and quick procedure is a suitable first-line alternative to other less successful or higher risk options.